Efeitos da estimulação elétrica neuromuscular nas circuitarias medulares inibitórias de sujeitos crônicos após acidente vascular cerebral - Motta-Oishi, Anna Amélia Pereira da [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The goal of this study was to analyse the effects of a neuromuscular electrical stimulation protocol considering the medullary inhibitory patterns, function and spasticity in 17 spastic hemiplegic subjects. These patients were divided in two groups. In the training group, the subjects received 30 minutes of the neuromuscular electrical stimulation on the tibialis anterior muscle of the affected side during 30 sessions. In each session it was considered a frequency of 30 Hz, pulse-width of 250 ms, 6 s on and off time, and the intensity depending on the threshold of the muscle contraction and the patient tolerance. In the control group zero intensity electrical stimulation was adopted. Before and final of the thirty sessions, reciprocal inhibition and pre synaptic inhibition were studied by using the H-reflex conditioning test while the homosynaptic depression was investigated trough of the H-reflex. In addition, the distance of the 2-minute walk test, motor recovery in the lower limb subscale of Fugl-Meyer, and spasticity according to the Ashworth modified scale were also measured. The results of the training group showed a statistically significant increase of the homosynaptic depression of 12.30 % (± 9.89 %) p = 0.03, the distance of 16.8 meters (± 9.17) p = 0.00, and the points in the Fugl-Meyer scale of 2.20 (± 1.93) p = 0.00...

O objetivo deste trabalho foi analisar os efeitos de um protocolo de estimulação elétrica neuromuscular nos padrões inibitórios medulares, na função e na espasticidade de sujeitos hemiplégicos espásticos. Para isto 17 pacientes portadores de hemiplegia espástica foram alocados em dois grupos. No grupo treino, os sujeitos receberam 30 sessões por 30 minutos cada de estimulação elétrica neuromuscular no músculo tibial anterior do hemicorpo afetado com frequência de 30 Hz, largura de pulso de 250 μs, tempo on 6 s, tempo off 6 s, e intensidade a depender da contração muscular e limiar de tolerância do paciente. No grupo controle a intensidade da estimulação elétrica foi mantida a zero. Inicialmente e ao final das 30 sessões foram avaliadas a inibição recíproca e inibição pré-sináptica através do teste condicionado do reflexo H e a depressão homossináptica através do reflexo H. Avaliou-se também a distância percorrida através do teste de caminhada de dois minutos, a recuperação motora através da subescala de membros inferiores da escala Fugl-Meyer e a espasticidade segunda a escala modificada de Ashworth. O grupo treino apresentou um aumento estatisticamente significante da depressão homossináptica 12.30 % (±9.89%) p=0.03, da distância percorrida com tamanho de efeito de 16.8 metros (±9.17) p=0.00, e aumento de 2.20 (±1.93) pontos na escala Fugl-Meyer p=0.00...
Keywords: Fisioterapia; Acidente vascular cerebral; Estimulação neural; Musculos; Hemiplegicos - Reabilitação; Physical therapy